Progress of Binder Structures in Silicon-Based Anodes for Advanced Lithium-Ion Batteries: A Mini Review - Zhu, Wenqiang; Zhou, Junjian; Xiang, Shuang; Bian, Xueting; Yin, Jiang; Jiang, Jianhong; Yang, Lishan (Frontiers in Chemistry, 2021)
Silicon (Si) has been counted as the most promising anode material for next-generation lithium-ion batteries, owing to its high theoretical specific capacity, safety, and high natural abundance. However, the commercial application of silicon anodes is hindered by its huge volume expansions, poor conductivity, and low coulombic efficiency. For the anode manufacture, binders play an important role of binding silicon materials, current collectors, and conductive agents, and the binder structure can significantly affect the mechanical durability, adhesion, ionic/electronic conductivities, and solid electrolyte interface (SEI) stability of the silicon anodes. Moreover, many cross-linked binders are effective in alleviating the volume expansions of silicon nanosized even microsized anodic materials along with maintaining the anode integrity and stable electrochemical performances. This mini review comprehensively summarizes various binders based on their structures, including the linear, branched, three-dimensional (3D) cross-linked, conductive polymer, and other hybrid binders. The mechanisms how various binder structures influence the performances of the silicon anodes, the limitations, and prospects of different hybrid binders are also discussed. This mini review can help in designing hybrid polymer binders and facilitating the practical application of silicon-based anodes with high electrochemical activity and long-term stability.